2021
DOI: 10.3758/s13414-021-02303-3
|View full text |Cite
|
Sign up to set email alerts
|

Distractor filtering is affected by local and global distractor probability, emerges very rapidly but is resistant to extinction

Abstract: Effects of statistical learning (SL) of distractor location have been shown to persist when the probabilities of distractor occurrence are equalized across different locations in a so-called extinction phase. Here, we asked whether lingering effects of SL are still observed when a true extinction phase, during which the distractor is completely omitted, is implemented. The results showed that, once established, the effects of SL of distractor location do survive the true extinction phase, indicating that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(77 citation statements)
references
References 48 publications
7
63
7
Order By: Relevance
“…The experiment was constructed using PsychoPy3 Version 2020.1.3 software (Peirce et al, 2019), and because of the COVID-19 pandemic restrictions experiments were run online using the Pavlovia web hosting service (Open Science Tools Limited, Nottingham, UK). However, previous studies have shown that similar online experiments replicated the pattern of results obtained with experiments conducted in the lab (Duncan & Theeuwes, 2020;Valsecchi & Turatto, 2021). The search arrays consisted of six red or green shapes (circles or diamonds) containing horizontal or vertical bars (Figure 1a).…”
Section: Stimuli and Proceduressupporting
confidence: 75%
See 1 more Smart Citation
“…The experiment was constructed using PsychoPy3 Version 2020.1.3 software (Peirce et al, 2019), and because of the COVID-19 pandemic restrictions experiments were run online using the Pavlovia web hosting service (Open Science Tools Limited, Nottingham, UK). However, previous studies have shown that similar online experiments replicated the pattern of results obtained with experiments conducted in the lab (Duncan & Theeuwes, 2020;Valsecchi & Turatto, 2021). The search arrays consisted of six red or green shapes (circles or diamonds) containing horizontal or vertical bars (Figure 1a).…”
Section: Stimuli and Proceduressupporting
confidence: 75%
“…The sample size (18 observers) was determined to match the one that produced a reliable target position effect in the extinction phase of Experiment 3 of our previous study (Valsecchi & Turatto, 2021). Since in the current study the exact task in the most relevant comparison (colour singleton search post-training) differed from the one (shape singleton search) used in the previous study, we also computed the observed power for the target position effect in the test phase using G*Power 3.1.9.7 (Faul et al, 2007).…”
Section: Participantsmentioning
confidence: 99%
“…This strengthens the inference that the observed attenuation of attentional capture is in truth caused by enhanced distractor suppression mechanisms. Other recent evidence supporting the conclusion that distractor frequency per se is a factor that modulates capture comes from the study by Valsecchi and Turatto (2021). This work demonstrated that distractor filtering is affected by both local and global distractor probability; when leaving the frequency of distractor occurrence at a particular location unchanged, increasing the overall distractor frequency in the search task (by increasing the frequency at other locations) leads to less capture at that particular location (Valsecchi & Turatto, 2021).…”
Section: Discussionmentioning
confidence: 54%
“…When confronted with many distractors, on the other hand, nonspecific suppression is rapidly in place. The observed time-course suggests that probabilistic expectations regarding distractor occurrence are formed very rapidly and speaks to the remarkable flexibility of second-order suppression, a flexibility that had so far only been reported for learned suppression based on predictable distractor characteristics (e.g., Valsecchi & Turatto, 2021; Wang & Theeuwes, 2020; Won et al, 2021).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation